2021
DOI: 10.3390/molecules26216683
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds and Antioxidant and Antimicrobial Activities of Selected Citrus Essential Oils Originated from Nepal

Abstract: Citrus species of plants are among the most commercially cultivated crops, mainly for their fruit. Besides, the generally consumed flesh inside the fruit, the peel is quite important too. Essential oils extracted from the peel have a history of being used by humankind for centuries. These essential oils are rich in antioxidants and antimicrobial agents. Comparative investigation of volatile constituents, and antioxidant and antimicrobial activities were undertaken. The essential oils were evaluated through gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
2
14
1
Order By: Relevance
“…EOs or most single components of EOs showed high efficacy against Salmonella typhimurium , E. coli O157: H7 and E. coli K88 , but had little inhibitory effect on Lactobacillus and Bifidobacterium . Bhandari et al [ 16 ] found that citrus EOs showed selective antibacterial activity in vitro. In agreement with those studies, the present study showed that the citrus EOs had selective antibacterial activity and inhibitory activity against pathogenic E. coli and Salmonella , but their activity varied with type of EO and the concentration added.…”
Section: Discussionmentioning
confidence: 99%
“…EOs or most single components of EOs showed high efficacy against Salmonella typhimurium , E. coli O157: H7 and E. coli K88 , but had little inhibitory effect on Lactobacillus and Bifidobacterium . Bhandari et al [ 16 ] found that citrus EOs showed selective antibacterial activity in vitro. In agreement with those studies, the present study showed that the citrus EOs had selective antibacterial activity and inhibitory activity against pathogenic E. coli and Salmonella , but their activity varied with type of EO and the concentration added.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the antibacterial activity of limonene, one of the major ingredients of essential oils in various plants and seeds [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major constituents of essential oil isolated from pomelo in Taiwan were 0.8% α -pinene, 2.7% β -pinene, 3.1% myrcene, 0.1% α -phellandrene, 0.4% β -ocimene, 87.5% limonene, and 0.4% linalool [ 17 ]. The constituents of essential oil isolated from peel of 3 pomelo cultivars in Nepal were 0.2–0.58% α -pinene, 0.77–2.17% sabinene, 0.15–6.09% β -pinene, 0.74–1.75 myrcene, 63.76–89.15% limonene, 0.35% β -phellandrene, 0.13–0.43% β -ocimene, and 0.35–2.65% linalool [ 20 ]. The constituents of essential oil of pomelo from Tunisia was 0.15% ± 0.06% α -pinene, 0.19% ± 0.01% sabinene,1.52% ± 0.06% β -pinene, 0.03% ± 0.00% β -myrcene, 95.4% ± 3.91% limonene, 0.26% ± 0.09% β -ocimene, and 0.09 ± 0.02 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%